HUBUNGAN ANTARA PENDIDIKAN MORAL DAN AGAMA DALAM TINJAUAN FILOSOFIS - Tiasari Siregar (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract: Religion, morals, and morality, have to do with human behavior judged from a normative point of view. Morals are very concerned with what to do, different from what is actually done. We can distinguish morals from prudential considerations, that is, about what should be done mainly for the benefit of the person who performed the (moral) act. In this case, wisdom emphasizes the importance of carrying out the main tasks. This research method uses a qualitative approach of the phenomenological-philosophical type. This research uses an interpretative-philosophical paradigm, namely the collection of data from nature (natural setting) as the main / core data through book readings in philosophical studies related to ontological, epistemological and moral axiological, and religious. Data in this study analyze philosophical views related to the relationship between moral and religious associated with education The source of the data in this study comes from book documents and studies of experts on the relationship between morals and religion, and what is the contribution of these two fields in education, it can be concluded that the meaning of education, morals and religion, also with the justification of morality and religion is instruments are important to incorporate into the curriculum. Moral education and religious education are specific forms of education, which are necessary to realize a complete education, but neither of which means will be the whole goal of educationKeywords: Moral and Religious education, philosophical review